Evaluasi Kinerja Crushing Plant Dan Belt Conveyor Dalam Pengolahan Dan Pengiriman Limestone Ke Storage Indarung di PT. Semen Padang - Fitri Eka Yulia; Raimon Kopa; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
PT. Semen Padang has 4 units of crushing plant there are crusher II, IIIA, IIIB, and VI. Production of limestone crusher in April 2017 is 692,755 tons, while the target of limestone crusher production is 804,749 tons so the target of limestone crusher production in PT. Semen Padang in April 2017 was not achieved. This is caused of the target crusher working hours are not achieved, frequent improvements in the crusher, and the change of usage belt conveyor lines. The purpose of this research is to get the performance value of crushing plant and belt conveyor, get the production capacity of belt conveyor, reveal the ideal crusher working system so we can get the ideal limestone crusher production.This research was combined between theory with field data, then we can get the problem solving approach, and the result of data processing will be analyzed for subsequent to be generated a recommendation.Based on the research result can be concluded. First, the performance of crushing plant and belt conveyor is not optimal because the work efficiency of limestone crusher II is 26,20%, crusher IIIA is 21,54%, and crusher IIIB is 28,33%. Second, the minimum production capacity of the belt conveyor is 1,409.7 tons/hour. Third, the ideal crusher working hours is 672 hours in a month so that the production of limestone crusher 810,992 tons in a month. Keyword: Production target, limestone crusher, belt conveyor